Extending networks with podcasting in the Caribbean - Tikasingh, Mike; Teelucksingh, Dev Anand (Technical Centre for Agricultural and Rural Cooperation, 2007)
The Trinidad and Tobago Computer Society uses podcasts to keep their members informed of the latest local technology stories